Abuse of authority or official authorities: a new view on the formation of private investigation methodology - Khlus, A.M. (Bulletin of the Karaganda University “Law Series”, 2022)
The technique of investigation of abuse of power or official powers is considered. The basis of its formation is formed by the forensic characteristics of this type of malfeasance, traditionally containing information borrowed mainly from criminal law and criminology. Such a provision, according to the author, does not contribute to understanding the presence of elements of the material structure in the system of this crime, and also does not ensure the disclosure of their content in the investigation process. Considering it, we conclude that the theoretical presentation of these crimes is insufficiently complete from the point of view of forensic science. The prevailing forensic characterization, the dominance of criminal law, and criminological knowledge about this act are incorrect from the standpoint of forensic reflection of its realities. The forensic characteristics of the analyzed crime should be based on knowledge about the common elements of its material structure. Information about these elements will form one of the main parts of the forensic characterization of abuse of power or official authority. Information about the elements of the material structure of the act in combination with their forensic characteristics creates a solid theoretical basis for building a private methodology for investigating the type of crime in question. Knowledge of the general material elements of a typical structure of abuse of power or official powers is necessary for the practical activity of investigating them. This allows not only to understand the structure of a specific act under investigation but also to identify the presence or absence of significant information on each of its elements. Correlation of information obtained in the process of investigative activity about the elements of the act under investigation with their description in the forensic characterization of the crime allows one to choose the direction of its investigation, put forward the appropriate versions, and determine the set of tactical means necessary to verify them.